2013
DOI: 10.1523/jneurosci.6070-11.2013
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen and Other GABAB Receptor Agents Are Allosteric Modulators of the CXCL12 Chemokine Receptor CXCR4

Abstract: CXCR4, a receptor for the chemokine CXCL12 (stromal-cell derived factor-1␣), is a G-protein-coupled receptor (GPCR), expressed in the immune and CNS and integrally involved in various neurological disorders. The GABA B receptor is also a GPCR that mediates metabotropic action of the inhibitory neurotransmitter GABA and is located on neurons and immune cells as well. Using diverse approaches, we report novel interaction between GABA B receptor agents and CXCR4 and demonstrate allosteric binding of these agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 50 publications
3
33
0
4
Order By: Relevance
“…As CXCL12 is the only known ligand for CXCR4, it is surprising that the Cxcr4 and Cxcl12 KOs have distinct phenotypes. CXCL12-independent functions of CXCR4 have not been demonstrated, but it has been recently shown that the neurotransmitter GABA directly binds CXCR4 and can act as an allosteric modulator (Guyon et al, 2013). Whether GABA or other potential modulators could influence CXCR4 function in the absence of CXCL12 in the ventral midbrain remains to be explored.…”
Section: Reelin Regulates Tangential Migration Of Da Neuronsmentioning
confidence: 99%
“…As CXCL12 is the only known ligand for CXCR4, it is surprising that the Cxcr4 and Cxcl12 KOs have distinct phenotypes. CXCL12-independent functions of CXCR4 have not been demonstrated, but it has been recently shown that the neurotransmitter GABA directly binds CXCR4 and can act as an allosteric modulator (Guyon et al, 2013). Whether GABA or other potential modulators could influence CXCR4 function in the absence of CXCL12 in the ventral midbrain remains to be explored.…”
Section: Reelin Regulates Tangential Migration Of Da Neuronsmentioning
confidence: 99%
“…Parmi les chimiokines, CXCL12/ SDF1 a beaucoup attiré l'attention notamment parce que l'un de ses deux récepteurs, le CXCR4, est également un des corécepteurs du VIH, le virus de l'immunodéficience humaine [9]. Une étude [10] avait montré que des agonistes et des antagonistes du récep-teur GABA B peuvent empêcher les effets chimioattractants du SDF1 sur des cellules cancéreuses exprimant spontanément le récepteur CXCR4, ce que nous avons confirmé [6] (Figure 1). De même, nous avons observé fortuitement qu'un antagoniste des récepteurs GABA B , le CGP 55845A, inhibe complètement les actions de la chimiokine sur les courants calciques membranaires de certains neurones du cerveau, effets connus pour être dus à la stimulation du CXCR4 [11].…”
Section: Le Baclofène Modifie Les Réponses Du Récepteur Cxcr4unclassified
“…KAP1, également connu sous les noms de TRIM28 (protéine à motif tripartite 28), TIF1 (facteur de transcription intermé-diaire 1), ou Krip-1 (KRAB-interacting protein 1), agit ensuite comme une plate-forme pour un complexe multimoléculaire qui réprime la transcription par l'induction d'hétérochromatine [3,4]. Le système KRAB/KAP1 a probablement d'abord évolué pour minimiser les perturbations du génome induites par l'invasion des rétroéléments [5], mais des données récentes indiquent qu'il contrôle également de multiples aspects de la physiologie des mammifères [6,7].…”
Section: Le Système Krab/kap1unclassified
See 2 more Smart Citations